An Examination of Turkish preschool curriculum’s effect on children’s concept acquisition - Temel, Zeynep Fulya; TORAN, MEHMET (Elsevier, 2012)
The aim of this study is to examine the effect of Turkish preschool curriculum on children’s concept acquisition. The research was carried out assessing children on three occasions, on September 2008, January 2009, and June 2009, respectively. Research was conducted on 24 children who were 5 years old, and schooled according to Turkish preschool curriculum. Bracken Basic Concept Scale-revised (BBCS-R), which has six subtests, was used as data collection instrument. For analyzing the data suitable statistic method was used. The results show that Turkish preschool curriculum has positive effect on children concept acquisition.
Keywords: Children; Concept acquisition; Curriculum; Turkish Preschool Curriculum